The models of strength-oriented loads periodization in mesocycles of training high-class racing skiers - Missina, S. S.; Adodin, N. V.; Kryuchkov, A. S.; Myakinchenko, E. B. (The Russian Journal of Physical Education and Sport, 2022)
Effective training process programming requires expedient periodization of differently orientated training loads. Information sources give the schemes of macrocycles creation for high-class racing skiers (RS), however, there is almost no information concerning the models of mesocycles creation at the stages of the preparatory period. That is why the aim of the research work was to create the model of strength-oriented loads periodization in mesocycles of training RS. Materials and research methods: Every day we gathered the results of the training loads among 11 RS, the leaders of the national sports teams of Russia (men and women) in terms of the centralized training and handled information with weekly gradation since May till September during the period since 2018 till 2020. All kinds of the loads are classified in accordance with three regimens of distant cyclic and 6 regimens of strength-oriented training. Results: At all stages of the preparatory period RS used the model of mesocycles according to 3+1 scheme, where 3 is "loading" and 1 is "unloading" microcycles. The duration of microcycles is 5-9 days. The scheme of the cyclic loads mesocycle, including aerobic-strength oriented method, was 3+1. The mesocycle of strength-oriented training was created according to 2+2 scheme. In the loading microcycles of strength-oriented mesocycle all regimens of power loads were combined with high volumes of low intensity cyclic load. However, the most specific high-intensity cyclic exercises were planned during the 3rd microcycle and were combined only with the supporting volumes of strength-oriented exercises. Starting from the involving till special-preparatory stage we gradually decreased the volumes of the exercises, fulfilled in slow "hypertrophic" and "maximal power" regimens, but increased the volumes of the exercises in high-intensity and quick regimens of muscles contraction. In terms of middle mountains we used relatively big volumes of high-intensity ("maximal power") slow regimens, but considerably smaller volumes of explosive and speed-strength oriented exercises. Conclusion: Received in the research work schemes of mesocycles creation taking into account the contingent of the respondents can be considered as "models" of periodization, which reflect the regularities of mesocycles planning at the stages of the preparatory period in modern cross-country skiing.